Vulnerability of farming communities to malaria in the Bole district, Ghana - Komlagan Mawuli Apélété Yao; Francis Obeng; Joshua Ntajal; Agbeko K. Tounou; Brama Kone (Parasite Epidemiology and Control, 2018)
Malaria contributes substantially to the poor health situation in the northern region of Ghana, especially in the Bole district. This paper is an outcome of a study, which assessed the factors that influenced the vulnerability of farming households to malaria, as well as the economic burden of the malaria prevalence in the Bole District, Ghana. The multiple linear regression model was used to analyze the determinants of household's vulnerability to malaria, and to examine the relationship between the non-parametric dependent variable and dichotomous independent variables. The outcome of the study revealed an increase in malaria cases during the rainy season. Total direct cost of malaria care, number of people comprising the farming household, support for malaria prevention, information on mosquito breeding and development, and absenteeism from farm emerged as the main factors, which influenced the households' vulnerability to malaria. Direct and indirect costs of malaria treatment have negatively affected the households' budget. In addition, malaria treatment cost represented a substantial portion of poor farming household income. The direct cost was estimated to GH₵ 4059, and the indirect cost was estimated to GH₵ 4654. It was recommended to the government of Ghana to expand the National Malaria Control Program to the household level and make National Health Insurance Scheme more efficient. Keywords: Malaria, Economic vulnerability, Malaria cost, Prevention